VALORACIÓN DE LA EMPRESA “TRACTO ORUGA”,DE LA CIUDAD DE LOJA, A TRAVÉS DEL MÉTODO DE FLUJOS DE CAJA DESCONTADOS, EN EL PERÍODO 2012-2020 - Cuenca Tandazo, Mayra del Rocio (2016)
The research was conducted in order to determine the value of the company "Tract Caterpillar"; of becoming a tool for decision making and as a means of obtaining investors for asset growth. That is why it was necessary for the evaluation to examine the financial situation of the company in the period 2012-2014, to develop an analysis of the internal and external environment to learn the indicators that affected the projection of the financial statements and analyze the flow method discounted cash. To be introduced in determining the valuation of the company's study concepts and definitions related to this subject, for it scientific, deductive, inductive, mathematical, statistical, analytical and synthetic methods are applied was made; as well as different techniques such as survey and interview instruments that provided information for the preparation of the assessment, allowing to obtain important observations that contributed to the interpretation of the results. Following the economic and financial situation of the company through the horizontal, vertical and application of financial indicators, which allowed visualize study economic behavior suffered by the company during the last three years financial analysis was examined. An analysis of the internal and external environment of the company "Caterpillar Tract", through exploration organizational environment, which allowed to obtain a broad view of the administration of it was developed. For the valuation of the company's evolution was observed during the years 2012-2014; and the method of discounted cash flows was applied, allowing the company to assess its ability to generate cash in the future. Then the value of the company to determine the sensitivity of the results in different scenarios were evaluated. As a result of the investigation it was determined that the company "Caterpillar Tract" normally reach a value of $ 941,196.35. In an optimistic scenario the value of the company amounts to $ 1,106,380.65, while in a pessimistic environment the value decreases to $ 771,978.52. Therefore the weighting value of the company "Caterpillar Tract" depending on the probability of occurrence of each scenario is $ 946,325.34. Finally it was concluded that the use of the method of discounted cash flows for the valuation of the company "Tract Caterpillar" was the most appropriate, since it allowed value it as a going concern and analyzing the possible scenarios that may arise in the implementation of the activities.